Implementation of HR Practices in University Teachers of Pakistan - Asghar, Rana Jimshaid; ., Arshad Zaheer; ., Asif Mughal; ., Sumaira Khalid (Information Management and Business Review, 2011)
The paper in your hand basically addresses the issue of organizational citizenship behavior in a particular context of Pakistani universities teachers. As education is most neglected area in Pakistan, we want to give better understanding of the concept of OCB. This paper will provide guidelines to researchers, teachers, education sector, and other education related institutions to form such policies which can help to increase the higher education standard. Our sample size is 274 university teachers from both public and private sector, including male and female, age ranges from 25 to 60 and teaching experience ranges from less than one year to 10 years. We have taken different HR practices implemented in universities and we studied their impact on the organizational citizenship behavior with mediating effect of organizational commitment it is found significantly positive from. So, we have concluded that by practicing all these independent variables in an effective and efficient way we can increase organizational commitment and it ultimately positively affect the employee positive and cooperative kind of behaviors i-e OCB